2022
DOI: 10.3390/molecules27041328
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nanotechnological Carriers for Ocular Delivery of Mangiferin: Preformulation Study

Abstract: (1) Background: Mangiferin (MGN) is a natural compound, showing anti-inflammatory and antioxidant activities for the potential treatment of eye diseases. The poor physicochemical features of MGN (low solubility and high instability) justify its nanoencapsulation into nanostructured lipid carriers (NLC) to improve its ocular bioavailability. (2) Methods: Firstly, MGN-NLC were prepared by the high shear homogenization coupled with the ultrasound (HSH−US) method. Finally, unloaded and MGN-loaded NLC were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…A mean particle size below 100 nm and entrapment efficiency reaching 88% were achieved, with sustained release (87%) over a period of 12 h. Mangiferin-NLCs increased the in vitro corneal permeation by 2.61-folds, and they were non-irritant to the rabbits' eyes, with a prolonged residence time on the corneal surface and in the conjunctival sac. Similar results were obtained by Santonocito et al (2022), who reported that 1-NLCs prepared using the solid lipid compritol 888 ATO and liquid lipid miglyol 812 enhanced the antioxidant properties of mangiferin, and were non-irritant to ocular tissues. Furthermore, a 1:1 phospholipidic complex of mangiferin was prepared for enhanced water solubility and oil-water partition coefficient, and then further loaded in NLCs composed of compritol 888 as solid lipid and labrafil M 2125 as liquid lipid (Khurana et al 2017b).…”
Section: Nanostructured Lipid Carrierssupporting
confidence: 87%
“…A mean particle size below 100 nm and entrapment efficiency reaching 88% were achieved, with sustained release (87%) over a period of 12 h. Mangiferin-NLCs increased the in vitro corneal permeation by 2.61-folds, and they were non-irritant to the rabbits' eyes, with a prolonged residence time on the corneal surface and in the conjunctival sac. Similar results were obtained by Santonocito et al (2022), who reported that 1-NLCs prepared using the solid lipid compritol 888 ATO and liquid lipid miglyol 812 enhanced the antioxidant properties of mangiferin, and were non-irritant to ocular tissues. Furthermore, a 1:1 phospholipidic complex of mangiferin was prepared for enhanced water solubility and oil-water partition coefficient, and then further loaded in NLCs composed of compritol 888 as solid lipid and labrafil M 2125 as liquid lipid (Khurana et al 2017b).…”
Section: Nanostructured Lipid Carrierssupporting
confidence: 87%
“…The nanoparticle size and the polydispersity index (PDI) were measured by photon correlation spectroscopy (PCS) using a Zeta Sizer Nano-ZS90 (Malvern Instrument Ltd., Worcs, UK) [ 48 ]. Analyses were performed using a 90° scattering angle at 20 ± 0.2 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenolic compounds are well-known for their antioxidant effects, which would be highly beneficial in the therapy of ocular degenerative diseases. However, these phytochemicals are usually characterized by poor aqueous solubility and an unfavorable pharmacokinetic profile, as reported for diosmin [ 203 ] and mangiferin [ 204 ]. Their encapsulation in NLCs led to an improvement of their disadvantageous physicochemical properties (e.g., low aqueous solubility), and further contributed to superior antioxidant activity (in the case of the mangiferin-loaded NLCs) and cytoprotective effects (for diosmin-loaded NLCs).…”
Section: Feasibility Of Lipid Nanoparticles In Ophthalmologymentioning
confidence: 99%